Communicating Climate Change A Guide for Educators - Armstrong, Anne K. (Cornell University Press, 2018)
Environmental educators face a formidable challenge when they approach climate change due to the complexity of the science and of the political and cultural contexts in which people live. There is a clear consensus among climate scientists that climate change is already occurring as a result of human activities, but high levels of climate change awareness and growing levels of concern have not translated into meaningful action. Communicating Climate Change provides environmental educators with an understanding of how their audiences engage with climate change information as well as with concrete, empirically tested communication tools they can use to enhance their climate change program.Starting with the basics of climate science and climate change public opinion, Armstrong, Krasny, and Schuldt synthesize research from environmental psychology and climate change communication, weaving in examples of environmental education applications throughout this practical book. Each chapter covers a separate topic, from how environmental psychology explains the complex ways in which people interact with climate change information to communication strategies with a focus on framing, metaphors, and messengers. This broad set of topics will aid educators in formulating program language for their classrooms at all levels. Communicating Climate Change uses fictional vignettes of climate change education programs and true stories from climate change educators working in the field to illustrate the possibilities of applying research to practice. Armstrong et al, ably demonstrate that environmental education is an important player in fostering positive climate change dialogue and subsequent climate change action.Thanks to generous funding from Cornell University, the ebook editions of this book are available as Open Access from Cornell Open (cornellopen.org) and other Open Access repositories.